(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The article deals with the issues of selection and application of geophysical methods related to improving the efficiency of studies of iron-bearing deposits of skarnmagnetite type, from the point of view of both field mapping and determining the elements of bedding of individual ore bodies and estimating forecasted reserves.